Ureteroiliac Artery Fistula in a Young Woman with Short Bowel Syndrome for Radiation Enteritis - Lidia Santarpia; Massimiliano Creta; Umberto Marcello Bracale; Roberto Ciccarelli; Fabrizio Pasanisi; Franco Contaldo; Ciro Imbimbo (Case Reports in Medicine)
Ureteral-iliac artery fistula is a rare and potentially life-threatening complication, typically occurring after radiation therapy in already surgically treated cancer patients. This case report describes the diagnostic challenges and the successful management, with the positioning of an intra-arterial prosthesis, of a fistula between the internal iliac artery and the left ureter presenting as massive hematuria in a young woman with history of total colectomy and pelvic radiotherapy for rectal cancer and subsequent wide ileal resections and bilateral ureteral stent positioning for radiation enteritis. Ureteroiliac artery fistulas require a prompt diagnosis and intervention, to avoid life threatening clinical events.